2016
DOI: 10.18295/squmj.2016.16.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Decisions to Perform Emergency Caesarean Sections at a University Hospital: Do obstetricians agree?

Abstract: abstract:Objectives: This study was undertaken to assess the degree of agreement amongst obstetricians regarding decisions to perform emergency Caesarean section (CS) procedures at a university hospital. Methods: This retrospective clinical audit was carried out on 50 consecutive emergency CS procedures performed between November 2012 and March 2013 on women with singleton pregnancies at the Sultan Qaboos University Hospital in Muscat, Oman. Data on each procedure were collected from electronic patient records… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…These three indications also appear to be important drivers responsible for increasing the CS rate in both developed and developing countries. [4,8,9] There were no women where the indication was 'maternal request' in this group.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…These three indications also appear to be important drivers responsible for increasing the CS rate in both developed and developing countries. [4,8,9] There were no women where the indication was 'maternal request' in this group.…”
Section: Discussionmentioning
confidence: 80%
“…Another study on evaluation of indications has shown that the most common disagreement was in interpreting fetal heart rate tracings . [8] All women at CHBAH are monitored in labour using a partogram. Dystocia is diagnosed when the labour does not progress for 4 hours in the active phase of labour.…”
Section: Discussionmentioning
confidence: 99%
“…Intrapartum CTG aims to detect fetal hypoxia related to acute or subacute events during labor that require medical management to reduce the risk of complications such as hypoxic-ischemic encephalopathy, cerebral palsy, and neonatal death 13 . Thus, it is justified that high-risk pregnant women with a CTG category III had a higher prevalence of cesarean section compared to CTG category I (90.0 vs. 42.9%), since in case of alteration in intrapartum fetal monitoring, it is prudent to perform maneuvers to improve maternal-fetal oxygenation, and if monitoring remains inadequate, it is recommended for immediate delivery to avoid metabolic acidemia and tissue injury 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Cesarean birth on request can describe as a delivery carried out for non-health indications (Nygaard & Cruikshank, 2003). Pillai et al (2016) revealed that the caesarian section (CS) rate in Oman increased gradually from 9.7% in 2000 to 15.7% in 2009 at Sultan Qaboos University Hospital(SQUH). According to the Health Information and Statistics Department-DG Planning and Studies under the Ministry of Health in Oman (2018), the rate of cesarean section deliveries in Oman increased from 9.7% in 2000 to 19.4% in 2018 of the total 89.071 childbirths (Omani and non-Omani) (MOH, 2018).…”
Section: Introductionmentioning
confidence: 99%